LEARNING PROBLEMS in a schizophrenic child. - Johnson, John L.; Juul, Kristen D. (Exceptional Children, 1960)
The article reports on the learning disability of schizophrenics children. Educating children with mental and emotional disability become a major concern due to its population increase. Several educational programs were organized to address this issue. This development programs helps teachers in identifying the type of teaching that a particular student needed. Based on teachers observation, children suffering from childhood schizophrenics shows an exceptional learning problems. Its main symptoms are retraction of interest from the environment, autistic thinking and other disturbances of thought. Many studies have been conducted to children with this disease who manages to still do good in school, but they were unable to identify the specific factors that interfere with their learning.